HOW PERSONALITY, CREATIVITY, AND INNOVATION SHAPE TEACHER PERFORMANCE IN INDONESIAN JUNIOR HIGH SCHOOLS - Julianti, Rina; Septiano, Renil; Sari, Laynita; Marwan, Marwan; Suryawan, Ryan Firdiansyah (Yayasan Education and Social Center, 2025)
Some of the problems identified in this study include: (1) Low discipline and weak responsibility among teachers at SMPN 1 Pagai Utara Selatan, (2) a Lack of innovation in teaching methods, and (3) Poor communication with parents, which affects overall teacher performance. This study aims to analyze the influence of personality, creativity, and innovation on teacher performance at SMPN 1 Pagai Utara Selatan. The research method used is a quantitative approach with an associative causal method. The sampling technique applied was total sampling involving 33 teachers as respondents. Partial hypothesis testing shows that personality (X1), creativity (X2), and innovation (X3) each have a positive and significant effect on teacher performance (Y), as evidenced by their respective t-count values being greater than t-table values. Simultaneous hypothesis testing also shows that personality, creativity, and innovation significantly affect teacher performance, as indicated by the F-count value being greater than the F-table value. Based on the analysis, personality, creativity, and innovation are important factors that affect teacher performance, both partially and simultaneously. Educational institutions are encouraged to strengthen these three aspects to improve teacher performance.